Recognizing the Needs and Challenges in Handling the Victims of Sexual Violence: Learning from the Experiences of ‘Forum Pengada Layanan’ - Atnike Nova Sigiro; Bagus Takwin (Jurnal Perempuan, 2021)
This article will describe the research’s result on the experiences of the members of ‘Forum Pengada Layanan’ or Service Provider Forum (FPL), a civil society initiative, in handling the victims of sexual violence. Through FPL's experience, this article will analyze the importance of legal protection and the availability of financial and human resources, in handling and protecting victims of sexual violence. This research was conducted using mixed methods, through surveys and in-depth interviews. This article concludes that the legal umbrella regarding the elimination of sexual violence with victims’ perspective would provide stronger foundation for protection, legal processes, and the availability of resources in handling cases of sexual violence in Indonesia.